Remoção de fluoretos em amostras de água utilizando lodo de ETA como adsorvente - Araujo, Diego Erieudes (Universidade Federal de São Carlos, 2016)
Water sludge is a solid waste produced during the water treatment. The volume of sludge produced in a water treatment plant can reach tons of material per month, depending of the quantity of water treated in the plant. Water sludge characteristics can vary depending of the water source and chemical products used in the water treatment. This material is rich in iron oxides, alum oxides, minerals and humic substances. Nowadays all this waste doesn’t have an application, being usually discharged in landfills, after a drying process, or into rivers. On the other hand, fluoride: an ion commonly founded in water samples from drilled wells. According to the current potability standard, administrative order number 2914/11 from Brazilian Govern Health Department, fluoride is necessary for water quality, being indispensable to avoid caries, primarily in children. However, in high concentrations – above 1,5 mg F?.L-1 –, fluoride causes health problems to the consumers, as dental fluorosis and skeletal fluorosis. Moreover, in a high concentration level, fluoride interferes or even hinders the application of this water to public supply, because most of the disposable technologies for fluoride removal have a high financial cost. That said, this work was planned to look for and combine a solution for both problems: utilization for water sludge and an alternative to fluoride removal with low cost. For this purpose, fluoride removal tests were done using fluoride standard samples in a jar-test equipment. These experiments were lead in different pH, to verify the pH influence in the fluoride removal process on the water sludge surface. After the experiments with the fluoride standard samples, a groundwater sample from the city of Capela do Alto, São Paulo state, was used to verify the efficiency of the material in a raw water sample with high fluoride, 2,8 ± 0,02 mg F?.L-1. The maximum adsorption result reached in fluoride standard sample was 0,36 ± 0,02 mg F?/g sludge, in pH 4. The minimum adsorption capacity was reached in pH 6, 0,30 ± 0,02 mg F?/g sludge. In the experiment with groundwater (pH 8,3), the maximum adsorption was 0,34 ± 0,02 mg F?/g sludge, showing the low pH influence in the fluoride adsorption onto water sludge.
Keywords: Lodo residual; Fluoretos; Sewage sludge; Fluorides; Reutilização de resíduo sólido; Tratamento de água; Reuse of solid waste; Water treatment; CIENCIAS EXATAS E DA TERRA